Isolation and Genetic Characterization of Toxoplasma gondii from Black Bears (Ursus americanus), Bobcats (Lynx rufus), and Feral Cats (Felis catus) from Pennsylvania. (8th January 2015) - Dubey, Jitender P.; Verma, Shiv K.; Calero‐Bernal, Rafael; Cassinelli, Ana B.; Kwok, Oliver C. H.; Van Why, Kyle; Su, Chunlei; Humphreys, Jan G.
Abstract: Toxoplasma gondii infects virtually all warm‐blooded hosts worldwide. Recently, attention has been focused on the genetic diversity of the parasite to explain its pathogenicity in different hosts. It has been hypothesized that interaction between feral and domestic cycles of T. gondii may increase unusual genotypes in domestic cats and facilitate transmission of potentially more pathogenic genotypes to humans, domestic animals, and wildlife. In the present study, we tested black bear ( Ursus americanus ), bobcat ( Lynx rufus ), and feral cat ( Felis catus ) from the state of Pennsylvania for T. gondii infection. Antibodies to T. gondii were found in 32 (84.2%) of 38 bears, both bobcats, and 2 of 3 feral cats tested by the modified agglutination test (cut off titer 1:25). Hearts from seropositive animals were bioassayed in mice, and viable T. gondii was isolated from 3 of 32 bears, 2 of 2 bobcats, and 2 of 3 feral cats. DNA isolated from culture‐derived tachyzoites of these isolates was characterized using multilocus PCR‐RFLP markers. Three genotypes were revealed, including ToxoDB PCR‐RFLP genotype #1 or #3 (Type II, 1 isolate), #5 (Type 12, 3 isolates), and #216 (3 isolates), adding to the evidence of genetic diversity of T. gondii in wildlife in Pennsylvania. Pathogenicity of 3 T. gondii isolates (all #216, 1 from bear, and 2 from feral cat) was determined in outbred Swiss Webster mice; all three were virulent causing 100% mortality. Results indicated that highly mouse pathogenic strains of T. gondii are circulating in wildlife, and these strains may pose risk to infect human through consuming of game meat.